2001
DOI: 10.1111/j.1365-2621.2001.tb15603.x
|View full text |Cite
|
Sign up to set email alerts
|

Extension of the Retail Display Life of Fresh Beef Packaged in Modified Atmosphere by Varying Lighting Conditions

Abstract: The effect of lighting conditions (darkness and either a standard supermarket fluorescent, a low-UV, color-balanced lamp, and the supermarket fluorescent with a UV filter) on the retail display life of fresh beef steaks packaged in a modified atmosphere was studied. Lighting without UV radiation led to a significant delay of meat spoilage, as assessed by surface color (a* and MetMb percentage), lipid oxidation (TBARS value), bacterial counts and sensory evaluation (discoloration and odor). Shelf life of fresh … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
74
0
7

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(87 citation statements)
references
References 21 publications
6
74
0
7
Order By: Relevance
“…Martínez et al (2006) reported that TBA-RS value above 1 had unacceptable off-odour. Djenane et al (2001) found that TBA-RS value of about 2 mg MDA/kg was required for consumer detection of rancidity. In fact, treated steaks reach a critical value only at the end of the display, resulting in an antioxidant AP ability between of 12.50-52.40% compared to untreated steaks; therefore, they would not present perceptible off-odours during display period, what is in accordance with sensory results.…”
Section: Lipid Oxidationmentioning
confidence: 99%
See 1 more Smart Citation
“…Martínez et al (2006) reported that TBA-RS value above 1 had unacceptable off-odour. Djenane et al (2001) found that TBA-RS value of about 2 mg MDA/kg was required for consumer detection of rancidity. In fact, treated steaks reach a critical value only at the end of the display, resulting in an antioxidant AP ability between of 12.50-52.40% compared to untreated steaks; therefore, they would not present perceptible off-odours during display period, what is in accordance with sensory results.…”
Section: Lipid Oxidationmentioning
confidence: 99%
“…The attributes studied were: ''red colour'', ''discoloration'', and ''offodour''. They were rated using a 5-point descriptive scale, according to Djenane et al (2001), using a paper scorecard. The attribute ''red colour'' was scored using an intensity of 5-point scale, in which 1 denoted extremely brilliant meat and 5 denoted extremely faded meat.…”
Section: Sensory Evaluationmentioning
confidence: 99%
“…The attribute off-odour was rated using a 5-point descriptive scale, in which: 1 = no off-odour, 2 = slight off-odour, 3 = little offodour, 4 = moderate off-odour, and 5 = strong off-odour (12).…”
Section: Sensory Evaluationmentioning
confidence: 99%
“…The second section was illuminated by a low-UV colorbalanced lamp (Promolux 1 Platinum L36 w; Market Group Ventures Inc., Shawnigan Lake, BC, Canada). The third section remained in the dark, and the light sources emission spectra was given by Djenane et al (2001). All illuminated samples were exposed to lighting continuously at 1000 lux at the surface.…”
Section: Sample Preparation and Display Conditionsmentioning
confidence: 99%
“…The use of a UV barrier in packaging material reduced light-induced discoloration of frozen minced beef during display (Andersen, Bertelsen, & Skibsted, 1989). Djenane, Sa´nchez-Escalante, Beltra´n, and Roncale´s (2001) reported that shelf life of fresh meat was extended from 12 to 22 days, a term similar to that when displayed in the dark, by using either a low-UV lamp or a standard fluorescent lamp with a UV filter.…”
Section: Introductionmentioning
confidence: 99%